2016
DOI: 10.1038/ncomms11996
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: SARI inhibits angiogenesis and tumour growth of human colon cancer through directly targeting ceruloplasmin

Abstract: SARI, also called as BATF2, belongs to the BATF family and has been implicated in cancer cell growth inhibition. However, the role and mechanism of SARI in tumour angiogenesis are elusive. Here we demonstrate that SARI deficiency facilitates AOM/DSS-induced colonic tumorigenesis in mice. We show that SARI is a novel inhibitor of colon tumour growth and angiogenesis in mice. Antibody array and HUVEC-related assays indicate that VEGF has an essential role in SARI-controlled inhibition of angiogenesis. Furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
86
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 41 publications
(50 reference statements)
5
86
0
Order By: Relevance
“…12 A previous study by our group indicated that the down-regulation of SARI inversely correlates with poor clinical outcomes in colon cancer patients. 15 In the present study, a decrease in intestinal SARI mRNA and protein expression accompanied the DSS treatment in the CAC model. Interestingly, injection of AOM significantly enhanced SARI expression both at the mRNA and protein level.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…12 A previous study by our group indicated that the down-regulation of SARI inversely correlates with poor clinical outcomes in colon cancer patients. 15 In the present study, a decrease in intestinal SARI mRNA and protein expression accompanied the DSS treatment in the CAC model. Interestingly, injection of AOM significantly enhanced SARI expression both at the mRNA and protein level.…”
Section: Discussionsupporting
confidence: 51%
“…14 The previous study by us demonstrated that SARI inhibiting tumour angiogenesis and colon tumour growth through directly targeting ceruloplasmin and inhibiting the HIF-1α/VEGF axis. 15 A recent study by us also determined the anti-tumour role of SARI-targeted demethylation system by inhibiting tumour proliferation, angiogenesis and promoting apoptosis in colon cancer. 16 However, the role of SARI in tumour-associated inflammation microenvironment is still elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Several cytokines, including VEGF, VEGF‐C, VEGF‐D, bFGF, and HGF, play a crucial role during tumor growth and angiogenesis . Inhibition of VEGF by upstream targets or neutralizing antibodies could efficiently inhibit tumor growth and cancer cell metastasis . In ovarian cancer, VEGF was upregulated and correlated with the clinical stage of the disease .…”
Section: Discussionmentioning
confidence: 99%
“…The invasion of 4T1 cells was evaluated using Transwell-24 units (pore size, 8 µm; EMD Millipore), as described previously with some modification (11). Briefly, the filter of the Transwell plate was covered with 50 µl matrigel (BD Biosciences, Franklin Lakes, NJ, USA).…”
Section: Methodsmentioning
confidence: 99%